2009
DOI: 10.1097/grf.0b013e3181b52930
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antenatal and Postpartum Maternal Mental Illness: How are the Children?

Abstract: Prospective studies that begin during pregnancy and follow the mothers and children into adolescence have shown that maternal mental illness during the antenatal and postpartum period can have long-lasting negative consequences on the developing child. The findings from these prospective studies and a discussion of the consistencies and inconsistencies in the current literature are presented. The effects of maternal anxiety and depression during the perinatal period on cognitive, behavioral, and psychologic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
129
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(140 citation statements)
references
References 26 publications
3
129
2
6
Order By: Relevance
“…55 In fact, one of the strongest predictors of PPD is untreated depression antepartum or early in the pregnancy. [56][57][58] These are similar findings to those of Meadows-Oliver et al who discovered that the rate of depression in adolescent mothers (between 46% and 54%) was significantly higher than in the general adolescent population (7.5%). 59 Given that unplanned pregnancies occur at a higher rate in this population, as opposed to women in general, the need for education and depression screening for adolescents is critically important.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…55 In fact, one of the strongest predictors of PPD is untreated depression antepartum or early in the pregnancy. [56][57][58] These are similar findings to those of Meadows-Oliver et al who discovered that the rate of depression in adolescent mothers (between 46% and 54%) was significantly higher than in the general adolescent population (7.5%). 59 Given that unplanned pregnancies occur at a higher rate in this population, as opposed to women in general, the need for education and depression screening for adolescents is critically important.…”
supporting
confidence: 80%
“…Research shows that maternal depression is associated with insecure maternal attachments, parenting problems, and unresponsive caregiving. 56 Offspring of depressed mothers have a greater frequency of addiction and behavioral problems and often suffer from depression themselves.…”
mentioning
confidence: 99%
“…Brand and Brennan (2009) and Wehby et al (2012) also found high risks for attention defi cit and hyperactivity problems in school age children with orofacial clefts. With regard to anxiety disorders, the data corroborate the fi ndings of Murray et al (2010), who identifi ed clinical indicators for anxiety in preschool children with orofacial clefts.…”
Section: Discussionmentioning
confidence: 99%
“…It is consensual that PPD predicts poorer language and IQ development in children and that this effect is found across childhood and adolescence [28,[37][38][39].…”
Section: Secondmentioning
confidence: 99%